Authentication of alert dissemination on friendship based mechanism - Abdulkarem Omar, Malek Najib (2014)
The disasters have always been the nightmare of people all over the world, and no exception for Malaysia. Some disasters are natural disasters and some of them are manmade disasters. In this research project, a new system has been proposed to disseminate and authenticate a trusted alert for natural disasters. The proposed system is Trusted Disaster Alert System (TDAS). This research project focuses on authenticating the disseminated alert based on friendship mechanism. Mainly, if people receive false alert, they may be scared. The fears of people and negative effects will be spread in the society. Moreover, the user may not believe any other disaster alert that could be a true disaster alert. When people ignore the disaster alert, they may face a maximum danger of that disaster. This research project discussed the existing disaster alert systems in information technology as well as the new proposed system architecture and implementation. Furthermore, a trust mechanisms and social networks have been analyzed to provide a friendship mechanism for TDAS. In this project, RSA, hashing and Graphical password authentication techniques were discussed to authenticate the disaster alerts. Indeed, they were implemented and analyzed to select one of them for the authentication purposes. TDAS is the first system using a web technology to disseminate a disaster alert based on friendship mechanism. TDAS is the first project that builds, tests, compare and validate RSA, hashing and Graphical password for disaster alert authentication. The aim of this research project is to reduce the false alert and disaster rumors. Moreover, people will be able to authenticate and verify the disaster alerts. This research project will reduce the death toll, the economic loss and the affections of natural disasters